Temporal and spatial microbiome dynamics across natural populations of the social spider Stegodyphus dumicola. Issue 2 (11th February 2022) - Busck, Mette M; Lund, Marie B; Bird, Tharina L; Bechsgaard, Jesper S; Bilde, Trine; Schramm, Andreas
Abstract: Host–symbiont interactions may form obligatory or facultative associations that are context dependent. Long-term studies on microbiome composition from wild populations should assess the temporal and spatial dynamics of host–microbe associations. We characterized the temporal and spatial variation in the bacterial microbiome composition in six populations of the social spider Stegodyphus dumicola for 2.5 years, using 16S rRNA gene amplicon sequencing of whole spiders. Individuals within a nest exhibit highly similar microbiomes, which remain stable over several generations and are not predictably affected by seasonal variation in temperature or humidity. This stability in nest microbiome is likely due to social transmission, whereas drift-like processes during new nest foundations explain variation in host microbiomes between nests. This is supported by the lack of obligate symbionts (i.e. no symbionts are present in all spider individuals). Quantitative PCR analyses showed that the bacterial load of individual spiders is stable in healthy nests but can increase dramatically in perishing nests. These increases are not driven by specific bacterial taxa but likely caused by loss of host immune control under deteriorating conditions. Spider nests show an annual survival rate of approximately 45%, but nest death is not correlated to microbiome composition, and the bacteria found in S. dumicola are not considered to be high virulence pathogens. Abstract : High temporal stability of the social spider microbiome, but nest death is often preceded by a massive increase in bacterial numbers.